Tyrosine Residues Regulate Multiple Nuclear Functions of P54nrb. Issue 4 (27th July 2016) - Lee, Ahn R.; Hung, Wayne; Xie, Ning; Liu, Liangliang; He, Leye; Dong, Xuesen
Abstract : The non‐POU‐domain‐containing octamer binding protein (NONO; also known as p54nrb) has various nuclear functions ranging from transcription, RNA splicing, DNA synthesis and repair. Although tyrosine phosphorylation has been proposed to account for the multi‐functional properties of p54nrb, direct evidence on p54nrb as a phosphotyrosine protein remains unclear. To investigate the tyrosine phosphorylation status of p54nrb, we performed site‐directed mutagenesis on the five tyrosine residues of p54nrb, replacing the tyrosine residues with phenylalanine or alanine, and immunoblotted for tyrosine phosphorylation. We then preceded with luciferase reporter assays, RNA splicing minigene assays, co‐immunoprecipitation, and confocal microscopy to study the function of p54nrb tyrosine residues on transcription, RNA splicing, protein–protein interaction, and cellular localization. We found that p54nrb was not phosphorylated at tyrosine residues. Rather, it has non‐specific binding affinity to anti‐phosphotyrosine antibodies. However, replacement of tyrosine with phenylalanine altered p54nrb activities in transcription co‐repression and RNA splicing in gene context‐dependent fashions by means of differential regulation of p54nrb protein association with its interacting partners and co‐regulators of transcription and splicing. These results demonstrate that tyrosine residues, regardless of phosphorylation status, are important for p54nrb function. J. Cell. Physiol. 232: 852–861, 2017. © 2016 Wiley Periodicals, Inc. Abstract : P54nrb (aka NONO) has various nuclear functions ranging from transcription, RNA splicing, DNA synthesis and repair. Although Tyr phosphorylation has been proposed to account for the multi‐functional properties of p54nrb, direct evidence on p54nrb as a phosphotyrosine protein remains unclear. Our studies demonstrate that the Tyr residues of p54nrb are not phosphorylated, but nevertheless significantly regulate p54nrb function by means of potential temporal and spatial regulation of p54nrb, resulting in altered interaction of p54nrb with various co‐regulatory splicing or transcriptional proteins.